Darker eggs of mosquitoes resist more to dry conditions: Melanin enhances serosal cuticle contribution in egg resistance to desiccation in Aedes, Anopheles and Culex vectors. - Luana C Farnesi; Helena C M Vargas; Denise Valle; Gustavo L Rezende (Public Library of Science (PLoS), 2017)
Mosquito vectors lay their white eggs in the aquatic milieu. During early embryogenesis water passes freely through the transparent eggshell, which at this moment is composed of exochorion and endochorion. Within two hours the endochorion darkens via melanization but even so eggs shrink and perish if removed from moisture. However, during mid-embryogenesis, cells of the extraembryonic serosa secrete the serosal cuticle, localized right below the endochorion, becoming the third and innermost eggshell layer. Serosal cuticle formation greatly reduces water flow and allows egg survival outside the water. The degree of egg resistance to desiccation (ERD) at late embryogenesis varies among different species: Aedes aegypti, Anopheles aquasalis and Culex quinquefasciatus eggs can survive in a dry environment for ≥ 72, 24 and 5 hours, respectively. In some adult insects, darker-body individuals show greater resistance to desiccation than lighter ones. We asked if egg melanization enhances mosquito serosal cuticle-dependent ERD. Species with higher ERD at late embryogenesis exhibit more melanized eggshells. The melanization-ERD hypothesis was confirmed employing two Anopheles quadrimaculatus strains, the wild type and the mutant GORO, with a dark-brown and a golden eggshell, respectively. In all cases, serosal cuticle formation is fundamental for the establishment of an efficient ERD but egg viability outside the water is much higher in mosquitoes with darker eggshells than in those with lighter ones. The finding that pigmentation influences egg water balance is relevant to understand the evolutionary history of insect egg coloration. Since eggshell and adult cuticle pigmentation ensure insect survivorship in some cases, they should be considered regarding species fitness and novel approaches for vector or pest insects control.